Better living through chemistry? A randomized, double‐blind controlled study evaluating the efficacy of plaque control and gingival health impacts of a novel stannous fluoride‐containing gel. Issue 4 (22nd November 2022) - Takesh, Thair; Goshtasbi, Arezou; Lin, Kairong; Yang, Susan Meishan; Wink, Cherie; Geisinger, Maria L.; Wilder‐Smith, Petra
Abstract: Background: Gingivitis is a nonspecific inflammatory lesion in response to the accumulation of oral biofilm and is a necessary precursor to periodontitis. Enhanced oral hygiene practices are necessary to reverse gingivitis and a dentifrice that could provide significant clinical reductions in plaque accumulation and gingival inflammation would be desirable to treat gingivitis and potentially prevent progression to periodontitis. This clinical study aimed to investigate the effect of a novel stannous fluoride‐containing dentifrice with 2.6% ethylenediamine tetra‐acetic acid (EDTA) as an antitartar agent to reduce Plaque Index (PI) and Gingival Index over a 3‐month study period. Methods: This double‐blind, randomized controlled clinical study evaluated plaque, gingival inflammation, and sulcular bleeding in patients using either a novel dental gel containing 0.454% stannous fluoride and 2.6% EDTA or a dentifrice with 0.24% sodium fluoride. Sixty subjects participated over a 3‐month period. Co‐primary endpoints were improvements in PI and Modified Gingival Index (mGI) from baseline values. No professional cleaning was performed during the study period. Results: All subjects in the study demonstrated statistically significant improvements in all measures of oral hygiene over the 3‐month study period. Subjects using the novel dental gel showed statistically significantly greater reductions in PI (ΔPI) [(−1.43 ± 0.34; −0.49 ± 0.13) ( p  < 0.00001)], mGI (ΔmGI) [(−1.11 ± 0.22; −0.16 ± 0.12) ( p  < 0.00001)], and modified sulcular bleeding index (ΔmSBI) [(−1.15 ± 0.18; −0.20 ± 0.07) ( p  < 0.00001)]. Conclusions: The novel dental gel demonstrated significant improvements in clinical parameters associated with gingivitis compared to a commercially available sodium fluoride dentifrice.